Effects of Deposition Time on the Synthesis and Characterisation of Lead Telluride (PbTe) Thin Films Deposited Using Electrochemical Techniques - Osolobri, Blessing Uyoyou; Omoyibo, Samuel Emuvokeraye; Ossai, Chukwunwike; Odenema, Ufuoma Alexander; Origho, Oghenebrirhie Anthony (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
Lead telluride (PBTE) is a narrow-bandgap IV–VI semiconductor widely used in infrared detectors and thermoelectric devices. Electrodeposition provides a cost-effective and scalable technique for producing PbTe thin films with tunable composition and structure, where parameters such as bath composition, deposition potential, temperature, and annealing influence phase purity and performance. Experimental findings show that PbTe films deposited for 10 seconds exhibited maximum light absorption (1.1253 a.u) at 308 nm in the UV region, while absorption decreased with increasing deposition time. Films deposited for 30 and 40 seconds displayed higher transmittance across visible and near-infrared wavelengths, indicating reduced light absorption. The film thickness increased slightly from 106.78 nm to 107.91 nm as deposition time rose from 10 to 40 seconds. The optical band gap also increased from 1.45 eV to 1.98 eV, suggesting tunability well above the bulk value (0.3 eV). Optical conductivity peaked at 0.00239 S/cm for films deposited for 10 seconds and decreased with longer deposition times, consistent with reduced charge transport in thicker films. The results indicate that shorter deposition times yield films with higher light absorption and conductivity, while longer times enhance transmittance and bandgap. The study concludes that electrodeposition is an economical and effective technique for producing high-quality PbTe thin films, with deposition time serving as a key factor in optimizing their optical and electronic properties for photovoltaic and optoelectronic applications